(3GdJMQjQ aj abg GdRjOjIs - (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s ((3CMeO Hf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd fYeJg SCdJ (B_ (3habc Gddg (B_ (3JdNjU ePGgH GdbGSe Hf EHQGgje hjMji Hf GdMSjf hChdGOgeG ai CHhGH Gdabg aCLHJc Ydi Pdc QLGA deG jMUd dc ef GdfaY s
(3BNQgG (B:s
(3aEf CSde Ndi SHjdg hEf CHj bJd hEf cGf cGaQkG ai GdCUd hdMb HOGQ GdMQH Je s
(3fSNI eUMMIs
(3cJHJ YfGhjjf GdCHhGH hGdahGJM HGdSejc Ydi WQJgG JedcGJs
(3cJHJ deGdcgG Ydi Hf eSYhO Hf YhGV GdUfYGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis